Penguatan Pengetahuan pada Bumdes dalam Rangka Implementasi PP No. 11 Tahun 2021 Tentang Bumdes Sebagai Peningkatan Kualitas Laporan Keuangan - Pipit Fitria; Ahmad Ali; Datice Anurahman; Muhamad Firmansyah; Siti Masripah; Idah Paridah (INTEGRITAS : Jurnal Pengabdian, 2026)
Community Service Program (PKM) by the PKM North West Java Master of Science in Accounting Team, Jenderal Soedirman University was carried out at BUMDes Arya Kamuning, Kaduela Village, Kuningan Regency, with the aim of increasing the literacy of BUMDes administrators and the community regarding the management of village business units. This activity focused on the dissemination of Government Regulation Government Regulation No. 11 of 2021 concerning BUMDes and the tax obligations that result from the establishment of BUMDes as a legal entity. The implementation methods included dissemination of materials, interactive discussions, simulations of financial report preparation, and technical assistance in the management of village businesses. The results of the activity showed an increase in the understanding of BUMDes administrators regarding regulations, tax obligations, and financial report management, which had an impact on the professionalism, transparency, and accountability of BUMDes management. This activity also encouraged the optimization of village potential, improved community welfare and opened opportunities for long-term assistance in forming highly competitive BUMDes.